Irisin Attenuates Myocardial Ischemia/Reperfusion Injury and Improves Mitochondrial Function Through AMPK Pathway in Diabetic Mice - Xin, Chao; Zhang, Zheng; Gao, Guojie; Ding, Liping; Yang, Chao; Wang, Chengzhu; Liu, Yanjun; Guo, Yufei; Yang, Xueqing; Zhang, Lijuan; Zhang, Lina; Liu, Yi; et al. (Frontiers in Pharmacology, 2020)
Aims: Several recent reports have shown irisin protects the heart against ischemia/reperfusion injury. However, the effect of irisin on I/R injury in diabetic mice has not been described. The present study was designed to investigate the role of irisin in myocardial ischemia-reperfusion (MI/R) injury in diabetic mice. Methods: A mouse model of diabetes was established by feeding wild type or gene-manipulated adult male mice with a high-fat diet. All the mice received intraperitoneal injection of irisin or PBS. 30mins after injection, mice were subjected to 30 min of myocardial ischemia followed by 3h (for cell apoptosis and protein determination), 24 h (for infarct size and cardiac function). Results: Knock-out of gene FNDC5 augmented MI/R injury in diabetic mice, while irisin treatment attenuated MI/R injury, improved cardiac function，cellular ATP biogenetics, mitochondria potential, and impaired mitochondrion-related cell death. More severely impaired AMPK pathway was observed in diabetic FNDC5-/- mice received MI/R. Knock-out of gene AMPK blocks the beneficial effects of irisin on MI/R injury, cardiac function, cellular ATP biogenetics, mitochondria potential, and mitochondrion-related cell death. Conclusions: Our present study demonstrated that irisin improves the mitochondria function and attenuates MI/R injury in diabetic mice through AMPK pathway.